Assessment of the lactulose-mannitol test in Crohn's disease. Issue 4 (April 1988) - Andre, F; Andre, C; Emery, Y; Forichon, J; Descos, L; Minaire, Y
Abstract : The mannitol-lactulose intestinal permeability test was evaluated in 100 healthy controls and 47 patients with Crohn's disease. These patients were further separated into three subgroups of increased activity (Harvey-Bradshaw index) and in two subgroups, with elective colonic lesions and associated ileal and colonic lesions. Results were given as percentages of urinary recoveries for mannitol (M), lactulose (L), and L/M ratio. As a whole, patients with Crohn's disease have lower mean M and higher mean L and mean L/M ratios than controls. The magnitude of alterations in M, L, and L/M increased with activity. The sensitivity of the test, however, reached interesting figures (67%:L and 86%:L/M) only in subgroup III which was composed of relapsing patients. Mean M was lower in patients with associated ileal lesion but, whatever the criterion (M, L, or L/M), the test does not provide any clue for the detection of a possible infraclinical associated ileal localisation.